The housing boom in Spain (1998-2007) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Over the years 1998-2007, the Spanish housing market underwent an enormous boom, with positive and negative consequences for the entire Spanish society. This paper analyses the dynamics of the housing market and the economic, social and environmental effects of the boom as well as emphasizing the poor results obtainedby the government housing policies implemented throughout this period.
Keywords: Housing boom; housing market; government housing policies